IMPLIKATUR DALAM SOAL CHOUKAI (JLPT N3 LISTENING) - Pratiwi, Desi Mentari; Aibonotika, Arza; Rahayu, Nana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The study focuses on analyzing the floats of Grice’s conversational maxim in choukai training applications namely JLPT N3 Listening. This study is aimed (1)to describe types of Grice’s conversational maxims are frequently floated in choukai training applications (2) to describe the implicature of the floats of the maxims. The writer employs descriptive qualitative approarch to reach and conclude the research findings in this study. In analyze the writer refers to Grice’s cooperative principle theory and the theory of means-ends analysis by Geoffrey Leech. Based on 16 data analyzed in this study obtained from choukai training applications, the writer finds that 3 of the data float maxim of quantity, 0 of data float maxim of quanlity, 7 of the data float maxim of relevance, and 6 of the data float maxim of manner. It is generally known that the purpose of floats the cooperation principle is to maintain courtesy in conversation.Key Words: Implicature, Cooperative Principle, Maxim